2017
DOI: 10.1111/fima.12182
|View full text |Cite
|
Sign up to set email alerts
|

School Holidays and Stock Market Seasonality

Abstract: Using school holiday data from 47 countries, we find a strong link between school holidays and market returns. Stock market returns in the month after major school holidays are 0.6% to 1% lower than in other months. This explains, but is not limited to, the “September effect.” In the United States, September is the only month that exhibits a negative average return over the past century. The postschool holiday effect remains even with monthly fixed effects. We explore the explanation that the effect is due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The authors did not find the confirmation of the January effect but confirmed the month of the years, the day of the week, the holiday, and the week of the year effects. The recent work Fang et al (2018) presents a strong link between school holidays and market returns across 47 countries. The authors demonstrate that the returns in the month after major school holidays are 0.6% to 1% lower than at other times.…”
Section: Traditional Marketsmentioning
confidence: 99%
“…The authors did not find the confirmation of the January effect but confirmed the month of the years, the day of the week, the holiday, and the week of the year effects. The recent work Fang et al (2018) presents a strong link between school holidays and market returns across 47 countries. The authors demonstrate that the returns in the month after major school holidays are 0.6% to 1% lower than at other times.…”
Section: Traditional Marketsmentioning
confidence: 99%